The ethics of teaching a casebook - Keith-Spiegel, Patricia (Lawrence Erlbaum, 2002)
The Ethics of Teaching provides a frank discussion of the most frequently encountered ethical dilemmas that can arise in educational settings, as well as tips on how to avoid these predicaments and how to deal with them when they do occur. The goal is to stimulate discussion and raise faculties' consciousness about ethical issues. Ethical dilemmas are presented as short, engaging case scenarios, most of which are based on actual situations, so as to furnish more realistic and interesting stimuli for individual reflection and group discussion. These scenarios offer the opportun
Keywords: College teachers : Professional ethics : Case studies; College teaching : Moral and ethical aspects : Case studies